Percutaneous balloon aortic valvuloplasty: palliative treatment for inoperable patients? - Klemen Dovč; Andrej Markota; Vojko Kanič; Mirko Bombek; Gregor Prosen (Acta Medico-Biotechnica, 2021)
Purpose: The number of elderly patients with severe aortic stenosis and comorbidities is increasing in the aging populations of “developed” countries. Unacceptably high perioperative mortality and morbidity makes the decision to undertake surgical aortic valve replacement in this group of patients difficult and unlikely. Development of less invasive procedures such as balloon aortic valvuloplasty and transcatheter aortic valve replacement is emerging as another treatment option.Case report: A 84-year-old female with previous left-sided hemiparesis after stroke and severe aortic stenosis presented with pulmonary edema to our institution. Non-invasive ventilation and inotropic support were unsuccessful. Balloon aortic valvuloplasty was done as as emergency procedure and she improved immediately. She was discharged after 25 days of inhospital treatment. She died 8 weeks later of unrelated reasons (infected decubitus and sepsis).Conclusion: Balloon aortic valvoluplasty might be used as temporary and interim therapeutical options for patients with severe aortic stenosis and acute left ventricular failure who have unacceptably high risks when aortic valve replacement or emergency transcatheter aortic valve implantation is considered. Balloon aortic valvuloplasty may be used as a bridge to both procedures.